THE EFFECTIVENESS OF PROBLEM-BASED LEARNING WITH THE SIMULATION LEARNING METHODS ONLINE PHYSIOTHERAPY: SYSTEMATIC REVIEW - Fadli, Arif; Susilowati, Scholastica Theresia (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: Problem-based learning (PBL) experiences face-to-face learning barriers for students due to natural disasters and the spread of disease. PBL requires innovation in the learning methods. This study purposed to summarize the existed literature data on the effectiveness of PBL with the simulation learning methods of online physiotherapy on students' knowledge aspects and skill competencies.Methods: Systematic review of research studies of randomized control trials, case-control studies, non-randomized control trials, and cohort studies of article search results on the Pubmed database, Google Scholar, Willey Online Library, Ovid, Science Direct. Researchers used qualitative descriptive data analysis.Results: 9 articles were included in the qualitative descriptive data analysis stage. 9 (100%) articles describe online physiotherapy simulation learning that is effective for increasing students' knowledge. 6 (66.7%) articles describe online physiotherapy simulation learning that is effective for increasing the competence of students' skills. 5 (55.6%) articles that describe operational guidelines for online physiotherapy simulation learning. Online physiotherapy simulation learning has the strength of learning methods for students in the aspect of flexibility in access to learning, low risk of patient-free learning, and audiovisual learning materials that are relevant to the needs of students. Meanwhile, online physiotherapy simulation learning has a disadvantageous learning method for students in terms of achieving depth of learning and limited learning support facilities.Conclusion: Problem-based learning with the simulation learning method of online physiotherapy is effective in increasing the knowledge and skill competence of students.